Peluang Potensial dan Dampak Visi Poros Maritim bagi Hubungan Indonesia-Australia - Sobarini, Eryn (Universitas Perrtahanan Indonesia (UNHAN), 2021)
World Maritime Axis is one of Indonesia’s policy to reach a new stage in the international system. One of World Maritime Axis’s pillars is Maritime Diplomacy which Indonesia Invites all countries to reduce the sources of conflict at the sea. There are influence betweet World Maritime Axis and the relationship between Indonesia and other countries, especially those with geographical proximity. Australia is one of the countries that have a geographical proximity with Indonesia. This studies using SWOT Analysis by Kearns and the concept of bilateral relations. Research method that used in this studies is content analysis. Based on the literatue researches conducted by researcher, it can be concluded that the opportunities and impacts of the World Maritime Axis affect bilateral relations between Indonesia and Australia as countries that have historical and geographical proximity.